2001
DOI: 10.1303/aez.2001.317
|View full text |Cite
|
Sign up to set email alerts
|

Close range sound communications of the oak platypodid beetle Platypus quercivorus (Murayama) (Coleoptera: Platypodidae).

Abstract: The oak platypodid beetle, Platypus quercivorus, stridulates both during premating behavior and when stressed, as well as spontaneously. When a female was put onto the bark surface of a male-infested log, she began to walk and produce an "approaching chirp," searching for a gallery entrance. When finding one, she entered it and tried to pull a male out. If the male's abdomen became visible, she appeared to push her frons against his elytral declivity and made a "premating buzz" that lasted about 5-10 s. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
1
9
1
Order By: Relevance
“…In P. koryoensis , the antennae are very short and clubbed, and a lot of sensory hairs are compactly arranged on the surface of the last antennal segment. It has been reported that the antennae may be used in some families during mating, or among a few beetles for defense (Ohya & Kinuura 2001;Kobayashi & Ueda 2002). 2003), they are often similar within any given family (Romoser & Stoffolano 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In P. koryoensis , the antennae are very short and clubbed, and a lot of sensory hairs are compactly arranged on the surface of the last antennal segment. It has been reported that the antennae may be used in some families during mating, or among a few beetles for defense (Ohya & Kinuura 2001;Kobayashi & Ueda 2002). 2003), they are often similar within any given family (Romoser & Stoffolano 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The antenna is a sensory organ that gathers information about the feel, sound, taste, smell, temperature and humidity of the beetle's environment (Ohya & Kinuura 2001). In P. koryoensis , the antennae are very short and clubbed, and a lot of sensory hairs are compactly arranged on the surface of the last antennal segment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gurevitz, 1975 1 4 male-initiated monogyny 1 Kirkendall, 19831 Kirkendall, 1983Kirkendall, 1983 1 1 Ytsma, 1988Jover, 1952Ohya and Kinuura, 2001 Kobayashi and Ueda, 2002Roberts, 1968 558 2006 1 2 2 3 Wilson and Hölldobler, 2005 Austroplatypus incomperus Kent and Simpson, 1992;Kent, 2002Kent and Simpson 1992Kent 2002 A. incomperus 2 4 resident non-resident resident 1 1 3 7 A. incomperus 12 Kent and Simpson 1992Kirkendall et al, 1997Hamilton 19643/4 Kasuya 1982A. incomperus Smith et al, 2009 A. incomperus Kasuya 1982 A. incomperus Kent and Simpson, 1992;Kent, 20025 Roberts, 1968Platypus calamus 5 2003200420065 200320065 20032006VI CT 1995Saunders and Knoke, 1967Norris and Chu, 1970Batra, 1985Batra, 1997 Mizuno and Kajimura, 20096 V 200320042006Hopping, 1961Ips subelongatus 1988…”
Section: Scolytus Rugulosusmentioning
confidence: 99%
“…Although sound communication is important as a cue for the mating behaviour of the beetles, 4) field experiments have indicated that chemical communication by using an aggregation pheromone was responsible for the mass attack on oaks by the beetles.…”
mentioning
confidence: 99%